Cost-benefit analysis of the use and recirculation of waste in a cocoa production system: a case study - Bonilla Montero, Jeannina (2021)
A cost-benefit investment analysis in the sustainable cocoa bean processing and drying system was carried out for organic chocolate.  Based on data provided by a family business that produces organic chocolate, the system, composed by a hybrid oven (designed by ITCR) and a family-size biodigester, built from the ground up, was put together, expecting that it could produce the necessary biogas volume to meet, both, the oven and manufacturing plant demand. Conventional profitability indicators were estimated to qualify the investment feasibility. The IRR was estimated at 37.13%, whose rate is higher than the expected return rates in the sector. It also favors the application to possible financing to cover the initial investment. The NPV was estimated at ₡ 24 267 557.56 giving a return of 9.35% per year on the initial investment of ₡ 18 289 745.76, being profitable for present generations (PG). Additionally, for future generations (FG), the NPV was estimated through the hyperbolic discount rate and gave a value of ₡ 40 983 896.51 with an annual return of 3.00% resulting profitable for both PGs and FGs.